Effects of supplemental 25-hydroxyvitamin D3 on growth performance, physiological responses, and gene expression of skeletal muscle growth of finishing beef cattle - Martins, Tainá E [UNESP]; Gouvêa, Vinícius N; Perdigão, Alexandre [UNESP]; Niehues, Maria Betania [UNESP]; Martins, Cyntia L [UNESP]; Millen, Danilo D [UNESP]; Acedo, Tiago S; Carvalho, Victor V; Tamassia, Luis F M; Arrigoni, Mario D B [UNESP] (Oxford University Press (OUP), 2025)
The objective of this experiment was to evaluate the effects of 25-hydroxyvitamin D3 (25(OH)D3) supplementation on growth performance, carcass characteristics, meat quality, and the expression of genes related to anabolism of skeletal muscle in finishing beef cattle. One hundred and twenty Nellore bulls (initial body weight [BW] = 376 ± 20 kg) were blocked by initial BW, allocated to 24 pens (5 bulls/pen) and pens were assigned to one of three treatments during a 96 d feeding experiment: control: high-concentrate basal diet (11% roughage; NEg = 1.16 Mcal/kg dry matter) with no supplemental 25(OH)D3 (0 mg of 25(OH)D3; n = 8 pens); basal diet containing supplemental 25(OH)D3 to provide 1 mg/animal/d (1 mg of 25(OH)D3; n = 8 pens), 3) basal diet containing supplemental 25(OH)D3 to provide 3 mg/animal/d (3 mg of 25(OH)D3; n = 8 pens). The dietary supplementation of 25(OH)D3 did not affect final BW, dry matter intake, average daily gain, and feed efficiency (P ≥ 0.32). Dressing percentage increased quadratically (P = 0.03) and Longissimus muscle area tended to increase quadratically (P = 0.09) with increasing levels of 25(OH)D3 supplementation. A treatment × day interaction was observed for plasma concentration of 25(OH)D3 (P < 0.001). No difference in plasma 25(OH)D3 concentration between treatments was observed at the beginning of the experiment (P > 0.05), but on days 37 and 95, plasma 25(OH)D3 was greater (P ≤ 0.05) for bulls fed 3 mg, followed by 1 mg, and 0 mg of 25(OH)D3. No effects of dietary supplementation of 25(OH)D3 were observed on meat quality attributes (P ≥ 0.24), except for meat pH that linearly increased (P < 0.01). The percentage of fat in the carcasses decreased linearly (P = 0.03) with increasing levels of 25(OH)D3 supplementation, followed by a numerical increase (P = 0.11) in the percentage of muscle. The gene expression of insulin-like growth factor-2 (IGF2), mammalian target of rapamycin, and myostatin tended (P ≤ 0.10), and IGF1 increased linearly (P = 0.04) with increasing levels of 25(OH)D3. In summary, the inclusion of 25-hydroxyvitamin D3 in feedlot diets may go beyond regulating calcium metabolism and meat quality only. Dietary supplementation of 1 mg of 25(OH)D3 for finishing beef cattle increased carcass dressing percentage and Longissimus muscle area by the upregulation of genes associated with skeletal muscle growth insulin-like growth factor-1 and 2, mammalian target of rapamycin, and myostatin.